Efforts to Improve Understanding of Compensation in Land Acquisition for Development in the Public Interest at SMA Taman Harapan I Bekasi - liza evita; M. Ryan Bakry; M.Kharis Umardani (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
The party entitled to the land needs to understand about compensation for the land, whose land will be used for development for public use. Partners do not understand fundamentally about compensation in land acquisition for development for public interest. This legal counseling activity is carried out using the participatory action method supported by lecture and discussion methods. This method is used to deliver cognitive extension materials such as the understanding, objectives, scope of land acquisition for development for public interest, objects of land acquisition, compensation and forms of compensation, land acquisition procedures, if there is no agreement in acquiring land for development for public interest. Based on the initial evaluation and final evaluation, significantly improved results were obtained so that it can be said that extension is one of the effective ways to provide an understanding of compensation in land acquisition for development in the public interest. It is recommended, for the future, it is necessary to conduct 1 (one) counseling specifically reviewing what if there is a disagreement in compensation maximum of 150 Indonesian.